Injection timing optimization in term of in-cylinder heat transfer analysis for direct injection hydrogen fueled engine - Khalaf I. Hamada; Md. Mustafizur, Rahman, Dr.; Abdul Rashid, Abd Aziz, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.